Indigenising ‘Research’ and Reconnecting Knowledge to Place – Indigenous Compositions, Songs, and Chants as Research Methods - Isaac Warbrick; Tom Johnson; Rachael Ka’ai-Mahuta; Meretini Bennett-Huxtable; Valance Smith (International Journal of Qualitative Methods)
The decolonisation and Indigenisation of research have been central to ongoing debates among Indigenous scholars, as they seek to reclaim knowledge systems disrupted by colonisation. In Aotearoa (New Zealand), Māori methodologies grounded in ancestral knowledge systems challenge Western paradigms and emphasise a connection between knowledge, place, and identity. Storytelling, in its many forms—including chants, songs, and other ‘artistic’ compositions—remains a culturally relevant, time-tested method of knowledge creation, preservation, and dissemination. This article explores the process of composing Māori waiata (songs and chants), as a research methodology and method for analysing, interpreting, and disseminating research findings. The research identifies three key contributions of Māori composition within a contemporary research setting. These learnings emerged from a qualitative study of the connections between Indigenous peoples and their natural environment. First, it recognizes composition as a traditional knowledge-building practice that reflects diverse tribal epistemologies while fostering deep engagement with participants’ narratives and settings. Second, it offers a way to connect people, knowledge, and environment, renewing bonds between Indigenous identity and ancestral landscapes. Third, it serves as a culturally resonant tool for Indigenous researchers and communities, empowering identity, preserving art forms, and ensuring that research findings are accessible and meaningful to those they are intended to serve. Ultimately, this article encourages Indigenous researchers to utilise their own respective methods of knowledge transmission and composition to re-imagine ‘research’ approaches that are meaningful and accessible for their own people.